COMMON FIXED POINT THEOREMS IN FUZZY METRIC SPACES - Patel, Raghu Nandan (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The concept of fuzzy metric space which was introduced by Kramosil and Michalek. Chang obtained a coincidence theorem for fuzzy mappings on topological spaces. Upadhyay and Choudhary [7] also proved a unique fixed point theorem for a self mapping and common fixed point theorem for four self mappings in the context of fuzzy metric spaces. Our work is subjected to establish two unique common fixed point theorems for three self mappings respectively in complete fuzzy metric spaces.